Acute positional vertigo in the emergency department—peripheral vs. central positional nystagmus - Koohi, Nehzat; Male, Amanda J.; Kaski, Diego (Frontiers in Neurology, 2023)
Introduction Benign paroxysmal positional vertigo (BPPV) is the most common cause of positional vertigo. However, positional vertigo can also be due to diseases affecting the central vestibular pathways, such as vestibular migraine. Accurate and timely diagnosis enables effective triage and management. Objectives To evaluate diagnoses made by emergency clinicians compared to acute vertigo specialists, in patients presenting to an emergency department (ED) with positional vertigo. Methods Following routine ED care, patients with a primary complaint of dizziness, vertigo, light-headedness or unsteadiness, underwent detailed neuro-otological assessment by acute vertigo specialists. Demographics and final diagnoses were recorded and analyzed. Results Of 71 consented patients (21−91 years; mean 56 years, ±16.7 years, 40 females), ED identified 13 with a peripheral cause of positional vertigo (mean 48.85 years, ±16.19, 8 females). Central positional nystagmus was not noted in any of the patients with positional vertigo seen by the ED clinicians. Acute vertigo specialists diagnosed nine patients with BPPV (age range 50-88 years, mean 66 years, ±12.22, 5 females), and six with central positional nystagmus (age range 23−59 years, mean 41.67 years, ±15.78, 6 females). Conclusion Positional vertigo should be assessed with positional maneuvers such as Dix-Hallpike and Roll tests in the ED to identify peripheral and central nystagmus features. Central causes are more common in younger females, with the presence of vomiting, and/or a background of motion sensitivity.